Arbitration of Approach-Avoidance Conflict by Ventral Hippocampus - Bryant, Kathleen G.; Barker, Jacqueline M. (Frontiers in Neuroscience, 2020)
When environmental cues or stimuli that represent both rewarding and aversive outcomes are presented, complex computations must be made in order to determine whether approach or avoidance is the better behavioral strategy. In many neuropsychiatric illnesses these computations can be skewed. In some instances, circumstances that may normally warrant avoidance instead promote approach, thus producing compulsive-like behavioral strategies that are inflexible in response to new or conflicting information. Alternatively, high sensitivity to aversion or low sensitivity to reward can result in the failure to achieve goals and loss of resilience that characterizes depressive disorders. Increases in compulsive-like behavior have been found to be associated with disrupted signaling in regions that regulate response to conflicting stimuli, including the hippocampus. Classic behavioral inhibition theories of hippocampus function in anxiety suggest that the hippocampus blocks aberrant behavior in response to anxiety related cues or stimuli. The hippocampus may act to block approach in the face of conflicting stimuli. Dysregulations of hippocampal function, as may be present in neuropsychiatric disorders, may therefore promote aberrant approach behavior. The ventral hippocampus (vHPC) subregion is key for coordinating this approach/avoidance conflict resolution, likely through its participation with cortico-striatal and mesolimbic circuits. We revisit Gray’s behavioral inhibition theory of HPC function, first posited in the 1980s, and interpret in the context of new knowledge on vHPC function gained through modern technology. Taken together with the extant, classical literature on hippocampal function, we propose that these new findings suggest that vHPC circuits balance behavioral response to conflicting stimuli in a manner that is both state- and context-dependent and, further, that disruption of specific vHPC circuits tips the balance in favor of biased approach or avoidance behavioral strategies.